Pesantren-Based School Quality Management: Innovative Strategies towards Superior Accreditation - Abdullah Yaqin; Moh. Rofiki (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Madrasah that is integrated with the dynamics of pesantren in the demand to maintain Islamic values while meeting the National Education Standards in order to maintain the title of superior accreditation. This condition requires targeted quality management as a strategic step so that the quality of education remains guaranteed systemically and sustainably. This study applied a qualitative approach with a single case study plan. Data collection was carried out through in-depth interviews, participatory observations, and document reviews involving madrasah heads, deputy madrasah heads, educators, students, and pesantren managers. The data analysis process refers to the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The findings of the study show that the desire for superior accreditation is formed through the integration between the formal mutual guarantee system and the pesantren culture that gives birth to a sustainable mutual culture. The integration between academic governance and the internalization of religious values is a key factor in maintaining consistency between institutional elements. Theoretically, this study offers an integrative model that combines the SPMI structural approach and the cultural TQM approach in the context of pesantren-based madrasas. Practically, the results of this study provide an operational framework for madrasah leaders and pesantren managers in harmonizing quality planning, cultural discipline-based supervision, and evaluation that includes academic aspects and character building. The integration between the formal madrasah system and the culture of pesantren is the main determinant in maintaining quality consistency and maintaining superior accreditation in an adaptive and sustainable manner.